Magnetic resonance imaging in late-life depression: vascular and glucocorticoid cascade hypotheses. - Sexton, C; Le Masurier, M; Allan, C; Jenkinson, M; McDermott, L; Kalu, U; Herrmann, L; Bradley, K; Mackay, C; Ebmeier, K (2012)
BACKGROUND: Late-life depression is a common and heterogeneous illness, associated with structural abnormalities in both grey and white matter. AIMS: To examine the relationship between age at onset and magnetic resonance imaging (MRI) measures of grey and white matter to establish whether they support particular hypotheses regarding the anatomy and aetiology of network disruption in late-life depression. METHOD: We studied 36 participants with late-life depression. Grey matter was examined using T(1)-weighted MRI and analysed using voxel-based morphometry. The hippocampus was automatically segmented and volume and shape analysis performed. White matter was examined using diffusion tensor imaging and analysed using tract-based spatial statistics. RESULTS: Later age at onset was significantly associated with reduced fractional anisotropy of widespread tracts, in particular the anterior thalamic radiation and superior longitudinal fasciculus. Earlier age at onset was associated with reduced hippocampal volume normalised to whole brain size bilaterally. However, no significant correlations were detected using hippocampal shape analysis or voxel-based morphometry. CONCLUSIONS: Overall, the results were compatible with the vascular hypothesis, and provided some support for the glucocorticoid cascade hypothesis.